On the zeros of polynomials with restricted coefficients - Zargar, B. A.; Gulzar, M. H.; Ali, M. (Annales Mathematicae Silesianae, 2023)
Let P(z) = Σj=0najzj be a polynomial of degree n such that an ≥ an-1 ≥ ... ≥ a1 ≥ a0 ≥ 0. Then according to Eneström-Kakeya theorem all the zeros of P(z) lie in |z| ≤ 1. This result has been generalized in various ways (see [1, 3, 4, 6, 7]). In this paper we shall prove some generalizations of the results due to Aziz and Zargar [1, 2] and Nwaeze [7].